Mid-range management theory : competence perspectives on modularity and dynamic capabilities - Sanchez, Ron; Heene, Aimé; Polat, Seçkin; Asan, Umut (Research in competence-based management ;, 2017)
This volume presents an epistemological argument for the essential function of mid-range theory in advancing management concepts that can be usefully applied by managers. Authors analyse two examples - modularity and dynamic capabilities.- Resumé vydavatel